Composite lubricating oil used in aluminum rolling process and preparation method thereof

Through the synergistic effect of the modified metal-organic framework and carnosic acid, a dense passivation film is formed, which solves the wear resistance and corrosion resistance problems of the lubricating oil and achieves efficient lubrication effect during aluminum rolling.

CN120665639APending Publication Date: 2025-09-19ZHUZHOU CHANGSHUANG PETROCHEMICAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510918773.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

The prior art does not modify the morphology and composition of molybdenum disulfide, resulting in insufficient wear resistance and corrosion resistance of the lubricating oil.

Method used

A modified metal-organic framework was prepared by reacting nanosheet molybdenum disulfide with 2-aminoterephthalic acid and nickel nitrate, and then carnosic acid was grafted through an amide reaction to form a wear-resistant antioxidant. Combined with extreme pressure antiwear agents and rust inhibitors, a dense passivation film was formed to improve lubrication performance.

Benefits of technology

It significantly improves the wear resistance and corrosion resistance of lubricating oil, reduces the friction coefficient, extends the service life of the roller, and improves the surface quality of the aluminum plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005482456860000111
    Figure BDA0005482456860000111
  • Figure BDA0005482456860000121
    Figure BDA0005482456860000121
Patent Text Reader

Abstract

The invention belongs to the technical field of lubricating oil manufacturing, and relates to composite lubricating oil used in an aluminum rolling process, which comprises the following components in parts by mass: 94-96 parts of base oil, 0.5-1.5 parts of an oiliness agent, 0.5-0.8 part of an extreme pressure anti-wear agent, 0.5-1.5 parts of a wear-resistant antioxidant, 0.5-2 parts of oleic acid diethanolamide and 0.5-1 part of an antirust agent. On the basis of the prior art, nano-sheet molybdenum disulfide is introduced and added into 2-aminoterephthalic acid and nickel nitrate to react to prepare a modified metal organic framework, then carnosic acid is grafted through an amide reaction to prepare the wear-resistant antioxidant, and a protective film can be formed on a friction interface through a sheet structure of molybdenum disulfide, so that the friction coefficient is reduced; the wear resistance is improved; a compact passive film is formed on the surface of aluminum metal through the synergistic effect of the extreme pressure anti-wear agent and the wear-resistant antioxidant, and the corrosion resistance and wear resistance of the composite lubricating oil used in aluminum plate rolling are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating oil manufacturing, and in particular relates to a composite lubricating oil used in an aluminum rolling process and a preparation method thereof. Background Art

[0002] Aluminum rolling is a core process in aluminum processing. It involves passing aluminum ingots through the gap between rotating rollers, where they undergo plastic deformation under the vertical pressure of the rollers, reducing their cross-section, thinning their thickness, and increasing their length. The friction between the rollers and the aluminum material generates a significant amount of deformation heat and frictional heat. During the rolling process, good process lubrication can effectively reduce rolling pressure, extend roller life, improve the surface quality of the rolled aluminum sheet, and provide rust protection between processes. Lubricating oil, the lubricating medium in the aluminum rolling process, forms a lubricating film on the aluminum surface, preventing direct contact between the machine and the workpiece, thereby reducing friction. Under the high loads and high temperatures of the rolling mill, the lubricant must possess multiple properties, including thermal oxidation stability, wear resistance, and lubricity. A single lubricant often fails to meet these requirements, so multiple additives are needed to achieve the performance requirements of the rolling process.

[0003] Chinese invention patent publication number CN115651741B discloses a lubricant for aluminum sheet and foil rolling and its preparation method, comprising light white oil, methyl oleate, dodecanol, graphene oxide-based nano-silica, isooctyl acid phosphate octadecylamine salt, and octadecenoic acid; wherein, by weight of the raw materials, the light white oil is 90-97 parts, the methyl oleate is 1-2 parts, the dodecanol is 0.5-1 part, the graphene oxide-based nano-silica is 0.1-0.2 parts, the isooctyl acid phosphate octadecylamine salt is 0.5-1 parts, and the octadecylamine salt is 0.1-0.3 parts. The present invention uses the synergistic effect of graphene oxide-based nano-silica, isooctyl acid phosphate octadecylamine salt, and octadecylamine acid to improve the oil film load-bearing capacity of the lubricant and provide excellent lubricity. However, the existing technology has a technical problem of not improving the wear resistance and corrosion resistance of lubricating oil by modifying the morphology and composition of molybdenum disulfide. Summary of the Invention

[0004] The purpose of the present invention is to provide a composite lubricant for use in aluminum rolling and a preparation method thereof, so as to solve the technical problem in the prior art that the wear resistance and corrosion resistance of the lubricant have not been improved by modifying the morphology and composition of molybdenum disulfide.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A composite lubricant for use in an aluminum rolling process, comprising the following components, in parts by mass: 94-96 parts of a base oil, 0.5-1.5 parts of an oiliness agent, 0.5-0.8 parts of an extreme pressure anti-wear agent, 0.5-1.5 parts of a wear-resistant antioxidant, 0.5-2 parts of oleic acid diethanolamide, and 0.5-1 part of a rust inhibitor;

[0007] The wear-resistant antioxidant is prepared by adding nanosheets of molybdenum disulfide to 2-aminoterephthalic acid and nickel nitrate to react to prepare a modified metal organic framework with molybdenum disulfide intercalation, and then grafting carnosic acid through an amide reaction;

[0008] The nanosheet molybdenum disulfide is prepared by ultrasonically exfoliating nano-molybdenum disulfide powder. The nanosheet molybdenum disulfide has 1 to 5 layers, a single layer rate of 70 to 80%, and a lateral size of 0.2 to 0.5 μm.

[0009] The modified metal organic framework is prepared by using 2-aminoterephthalic acid as an organic ligand and nickel ions of nickel nitrate to connect the organic ligand. The molar ratio of molybdenum disulfide to nickel nitrate is (1-2):1.

[0010] The base oil is any one of synthetic oil and light mineral oil, the specific model of the synthetic oil is PANESTER0418, and the specific model of the light mineral oil is 10#; the oiliness agent is any one or more combinations of methyl oleate, pentaerythritol oleate, and trimethylolpropane oleate; the extreme pressure and anti-wear agent is any one of dialkyl dithiophosphate zinc and di-n-butyl phosphite; and the rust inhibitor is any one of dodecenylsuccinic acid and barium dinonylnaphthalenesulfonate.

[0011] The preparation method of the wear-resistant antioxidant comprises the following steps:

[0012] S11. Add 1 to 2 parts by mass of molybdenum disulfide powder and 100 to 150 parts of N-methylpyrrolidone to a reaction kettle, heat and shear, stir and disperse under a nitrogen atmosphere, keep warm and perform ultrasonic treatment, centrifuge and filter to obtain the supernatant, vacuum dry, and dialyze in deionized water to obtain a nanosheet molybdenum disulfide dispersion;

[0013] S12, dissolving 0.1-0.4 parts of 2-aminoterephthalic acid in 30-50 parts of N,N'-dimethylformamide, adding 0.1-0.2 parts of nanosheet molybdenum disulfide dispersion and 0.1-0.3 parts of nickel nitrate, heating the mixture for reaction, centrifuging and drying under vacuum to obtain a modified metal organic framework;

[0014] S13. Add 0.5 to 1 parts of the modified metal organic framework to 50 to 60 parts of xylene by mass, add 0.1 to 0.5 parts of carnosic acid, heat and react under vacuum conditions, remove the xylene by rotary evaporation, and prepare a wear-resistant antioxidant.

[0015] Preferably, the temperature in S11 is raised to 90-95° C. under a nitrogen atmosphere, and the dispersion is sheared and stirred at 2000-3000 rpm for 15-30 min, and ultrasonicated at an ultrasonic frequency of 30-50 kHz for 0.5-2 h. The concentration of the molybdenum disulfide dispersion is 1-5 mg / mL.

[0016] Preferably, the molar ratio of 2-aminoterephthalic acid to nickel nitrate in S12 is (1.9-2.5): (1-1.2), and the temperature is raised to 80-90° C. and the reaction is carried out for 10-12 hours.

[0017] Preferably, in S13, the temperature is raised to 110-130° C. and the reaction is carried out for 1-2 hours to allow the carboxyl group of carnosic acid to undergo an amide reaction with the amino group of the modified metal organic framework, thereby loading the modified metal organic framework with carnosic acid.

[0018] A method for preparing a composite lubricating oil used in an aluminum rolling process comprises the following steps:

[0019] S1. Filter the base oil and add it to a reactor. Heat it to 60-70°C. Add extreme pressure anti-wear agent and wear-resistant antioxidant and stir it at high speed while keeping it warm. Then add oleic acid diethanolamide, rust inhibitor and oiliness agent. Keep it warm and stir it. Cool and filter it. Fill it into a can to prepare a composite lubricant for aluminum rolling.

[0020] Preferably, after adding extreme pressure anti-wear agent and wear-resistant antioxidant to S1, high-speed shear stirring is carried out at a speed of 5000-10000 rpm for 1-2 hours, and after adding oleic acid diethanolamide, rust inhibitor and oiliness agent, stirring is carried out at a speed of 1000-2000 rpm for 1-2 hours.

[0021] An application of a composite lubricating oil for aluminum rolling process, for lubricating an aluminum cold rolling mill, comprises the following steps:

[0022] S21. Add the composite lubricating oil used in the aluminum rolling process into an oil tank with a temperature of 40-60°C, heat and atomize it into 1-3 μm droplets through an oil and gas generator, and then spray it from a nozzle to the contact area between the aluminum plate and the cold rolling mill roller through compressed air, and control the oil film thickness to 0.5-1.2 μm.

[0023] Preferably, the pressure of the compressed air in S21 is 0.5-3 MPa, the roughness of the upper and lower rollers of the cold rolling mill is Ra=1-2 μm, and the rolling speed is 300-500 m / min.

[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0025] 1. The present invention peels off layered molybdenum disulfide through ultrasonic peeling to form a nanosheet molybdenum disulfide dispersion, then adds 2-aminoterephthalic acid and nickel nitrate to react to obtain a modified metal-organic framework with molybdenum disulfide intercalation, and finally grafts carnosic acid to obtain a wear-resistant antioxidant. The flaky structure of molybdenum disulfide can form a protective film at the friction interface, thereby reducing the friction coefficient and improving the wear resistance. The surface of the modified metal-organic framework with molybdenum disulfide intercalation contains amino groups, which can form a chemical bond with the aluminum metal surface to form a dense passivation film, thereby preventing corrosive substances from further corroding the aluminum metal part exposed by rolling. Carnosic acid, as a natural antioxidant, has the properties of high temperature resistance and good oil solubility. The thermal stability of carnosic acid is improved by grafting it into the modified metal-organic framework through an amide reaction. Sage synergistically scavenges free radicals and reduces boundary friction and wear, which can further improve the corrosion resistance and wear resistance of the wear-resistant antioxidant.

[0026] 2. Based on the existing technology, the present invention introduces a modified metal-organic framework with molybdenum disulfide intercalation prepared by reacting nanosheet molybdenum disulfide with 2-aminoterephthalic acid and nickel nitrate, and then grafts carnosic acid to prepare a wear-resistant antioxidant through an amide reaction. Through the synergistic effect of the extreme pressure anti-wear agent and the wear-resistant antioxidant, a dense passivation film is formed on the surface of the aluminum metal, thereby improving the corrosion resistance of the composite lubricant. DETAILED DESCRIPTION

[0027] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0028] Example 1: A composite lubricant for aluminum rolling in this example comprises the following components: 960 g of base oil, 7 g of oiliness agent, 8 g of extreme pressure anti-wear agent, 7 g of wear-resistant antioxidant, 10 g of oleic acid diethanolamide, and 8 g of rust inhibitor.

[0029] Among them, the nanosheet molybdenum disulfide is made by ultrasonically exfoliating nano-molybdenum disulfide powder. The monolayer rate of the nanosheet molybdenum disulfide is 70% and the lateral size is 0.2μm. The molar ratio of molybdenum disulfide and nickel nitrate in the modified metal-organic framework is 1.1:1.

[0030] The base oil is PANESTER 0418; the oiliness agent is prepared by mixing methyl oleate and pentaerythritol oleate in a mass ratio of 1:3; the extreme pressure anti-wear agent is zinc dialkyl dithiophosphate; and the rust inhibitor is dodecenylsuccinic acid.

[0031] The preparation method of the wear-resistant antioxidant of this embodiment comprises the following steps:

[0032] S11, 1.5g of molybdenum disulfide powder and 150g of N-methylpyrrolidone were added to a reactor, the temperature was raised to 95°C under a nitrogen atmosphere, sheared and stirred at 3000rpm for 15min, ultrasonicated at 40kHz for 1h under a heat preservation state, the supernatant was centrifuged and filtered, vacuum dried, and dialyzed into deionized water to obtain a nanosheet molybdenum disulfide dispersion with a concentration of 3mg / mL;

[0033] S12, dissolving 0.33 g of 2-aminoterephthalic acid in 35 g of N,N'-dimethylformamide, adding 50 mL of a nanosheet molybdenum disulfide dispersion containing 0.15 g of molybdenum disulfide and 0.25 g of nickel nitrate, heating to 80° C. for 12 h, centrifuging and drying in vacuum to obtain a modified metal organic framework;

[0034] S13. Add 0.5 g of the modified metal organic framework to 60 g of xylene, add 0.3 g of carnosic acid, raise the temperature to 110° C. under vacuum conditions, react for 2 h, and remove the xylene by rotary evaporation to obtain a wear-resistant antioxidant.

[0035] A method for preparing a composite lubricant for use in an aluminum rolling process according to this embodiment includes the following steps:

[0036] S1. Filter the base oil and add it to a reactor. Raise the temperature to 60°C. Add an extreme pressure anti-wear agent and a wear-resistant antioxidant, then keep the temperature and stir at a speed of 10,000 rpm for 2 hours. Then add oleic acid diethanolamide, a rust inhibitor and an oiliness agent, stir at a speed of 2,000 rpm for 2 hours, cool and filter, and can to obtain a composite lubricant for aluminum rolling.

[0037] The present embodiment provides an application of a composite lubricating oil for aluminum rolling, which is used for lubricating an aluminum cold rolling mill, and includes the following steps:

[0038] S21. Add the composite lubricating oil used in the aluminum rolling process into an oil tank at a temperature of 40°C, heat and atomize it into 1 μm droplets through an oil and gas generator, and then spray it from a nozzle to the contact area between the aluminum plate and the cold rolling mill roller through compressed air at a pressure of 2 MPa. The roughness of the upper and lower rollers of the cold rolling mill is Ra = 1.1 μm, and the rolling speed is 400 m / min. The oil film thickness is controlled to be 0.8 μm.

[0039] Example 2: A composite lubricant for aluminum rolling in this example comprises the following components: 950 g of base oil, 10 g of oiliness agent, 8 g of extreme pressure anti-wear agent, 12 g of wear-resistant antioxidant, 10 g of oleic acid diethanolamide, and 10 g of rust inhibitor.

[0040] Among them, the nanosheet molybdenum disulfide is made by ultrasonically exfoliating nano-molybdenum disulfide powder. The monolayer rate of the nanosheet molybdenum disulfide is 76% and the lateral size is 0.5μm. The molar ratio of molybdenum disulfide and nickel nitrate in the modified metal-organic framework is 1.5:1.

[0041] The base oil is 10# light mineral oil; the oiliness agent is prepared by mixing pentaerythritol oleate and trimethylolpropane oleate in a mass ratio of 1:1; the extreme pressure anti-wear agent is di-n-butyl phosphite; and the rust inhibitor is barium dinonylnaphthalenesulfonate.

[0042] The preparation method of the wear-resistant antioxidant of this embodiment comprises the following steps:

[0043] S11, 1g of molybdenum disulfide powder and 150g of N-methylpyrrolidone were added to a reactor, the temperature was raised to 95°C under a nitrogen atmosphere, sheared and stirred at 3000rpm for 15min, ultrasonicated at an ultrasonic frequency of 50kHz for 0.5h under a heat preservation state, and the supernatant was centrifuged and filtered, vacuum dried, and dialyzed into deionized water to obtain a nanosheet molybdenum disulfide dispersion with a concentration of 1mg / mL;

[0044] S12, dissolving 0.15 g of 2-aminoterephthalic acid in 30 g of N,N'-dimethylformamide, adding 100 mL of a nanosheet molybdenum disulfide dispersion containing 0.1 g of molybdenum disulfide and 0.12 g of nickel nitrate, heating to 90° C. and reacting for 10 h, centrifugally filtering, and vacuum drying to obtain a modified metal organic framework;

[0045] S13. Add 1 g of the modified metal organic framework to 60 g of xylene, add 0.1 g of carnosic acid, raise the temperature to 130° C. under vacuum conditions, react for 2 h, and remove the xylene by rotary evaporation to obtain a wear-resistant antioxidant.

[0046] A method for preparing a composite lubricant for use in an aluminum rolling process according to this embodiment includes the following steps:

[0047] S1. Filter the base oil and add it to a reactor. Raise the temperature to 70°C. Add an extreme pressure anti-wear agent and a wear-resistant antioxidant, keep the temperature high, and stir at a speed of 6000 rpm for 1 hour. Then add oleic acid diethanolamide, a rust inhibitor, and an oiliness agent. Stir at a speed of 1000 rpm for 1 hour. Cool and filter, and can to obtain a composite lubricant for aluminum rolling.

[0048] The present embodiment provides an application of a composite lubricating oil for aluminum rolling, which is used for lubricating an aluminum cold rolling mill, and includes the following steps:

[0049] S21. Add the composite lubricating oil used in the aluminum rolling process into an oil tank at a temperature of 45°C, heat and atomize it into 3μm droplets through an oil and gas generator, and then spray it from a nozzle to the contact area between the aluminum plate and the cold rolling mill roller through compressed air with a pressure of 0.5MPa. The roughness of the upper and lower rollers of the cold rolling mill is Ra=2μm, and the rolling speed is 300m / min. The oil film thickness is controlled to be 1.2μm.

[0050] Example 3: A composite lubricant for aluminum rolling in this example comprises the following components: 945 g of base oil, 5 g of oiliness agent, 5 g of extreme pressure anti-wear agent, 15 g of wear-resistant antioxidant, 20 g of oleic acid diethanolamide, and 10 g of rust inhibitor.

[0051] Among them, the nanosheet molybdenum disulfide is made by ultrasonically exfoliating nano-molybdenum disulfide powder. The monolayer rate of the nanosheet molybdenum disulfide is 78% and the lateral size is 0.2μm. The molar ratio of molybdenum disulfide and nickel nitrate in the modified metal-organic framework is 1.8:1.

[0052] The base oil is PANESTER 0418, and the specific model of the light mineral oil is 10#; the oiliness agent is prepared by mixing methyl oleate, pentaerythritol oleate and trimethylolpropane oleate in a mass ratio of 1:1:1; the extreme pressure and anti-wear agent is zinc dialkyl dithiophosphate; and the rust inhibitor is dodecenylsuccinic acid.

[0053] The preparation method of the wear-resistant antioxidant of this embodiment comprises the following steps:

[0054] S11, 2g of molybdenum disulfide powder and 150g of N-methylpyrrolidone were added to a reactor, the temperature was raised to 90°C under a nitrogen atmosphere, sheared and stirred at 2500rpm for 20min, ultrasonicated at 30kHz for 2h under a heat preservation state, centrifuged and filtered to obtain the supernatant, vacuum dried, and dialyzed in deionized water to obtain a nanosheet molybdenum disulfide dispersion with a concentration of 5mg / mL;

[0055] S12, dissolving 0.3 g of 2-aminoterephthalic acid in 40 g of N,N'-dimethylformamide, adding 40 mL of a nanosheet molybdenum disulfide dispersion containing 0.2 g of molybdenum disulfide and 0.2 g of nickel nitrate, heating to 85° C. for 10 h, centrifuging and drying in vacuum to obtain a modified metal organic framework;

[0056] S13. Add 1 g of the modified metal organic framework to 50 g of xylene, add 0.4 g of carnosic acid, raise the temperature to 110° C. under vacuum conditions, react for 1 h, and remove the xylene by rotary evaporation to obtain a wear-resistant antioxidant.

[0057] A method for preparing a composite lubricant for use in an aluminum rolling process according to this embodiment includes the following steps:

[0058] S1. Filter the base oil and add it to a reactor. Raise the temperature to 65°C, add an extreme pressure anti-wear agent and a wear-resistant antioxidant, keep the temperature, and stir at a speed of 5000 rpm for 1 hour. Then add oleic acid diethanolamide, a rust inhibitor, and an oiliness agent, stir at a speed of 1000 rpm for 2 hours, cool and filter, and can to obtain a composite lubricant for aluminum rolling.

[0059] The present embodiment provides an application of a composite lubricating oil for aluminum rolling, which is used for lubricating an aluminum cold rolling mill, and includes the following steps:

[0060] S21. Add the composite lubricating oil used in the aluminum rolling process into an oil tank at a temperature of 50°C, heat and atomize it into 2μm droplets through an oil and gas generator, and then spray it from a nozzle to the contact area between the aluminum plate and the cold rolling mill roller through compressed air with a pressure of 0.9MPa. The roughness of the upper and lower rollers of the cold rolling mill is Ra=1.6μm, and the rolling speed is 300m / min. The oil film thickness is controlled to be 0.8μm.

[0061] Example 4: A composite lubricant for aluminum rolling in this example comprises the following components: 960 g of base oil, 10 g of oiliness agent, 5 g of extreme pressure anti-wear agent, 15 g of wear-resistant antioxidant, 5 g of oleic acid diethanolamide, and 5 g of rust inhibitor.

[0062] Among them, the nanosheet molybdenum disulfide is made by ultrasonically exfoliating nano-molybdenum disulfide powder. The monolayer rate of the nanosheet molybdenum disulfide is 80% and the lateral size is 0.5μm. The molar ratio of molybdenum disulfide and nickel nitrate in the modified metal-organic framework is 1.3:1.

[0063] The base oil is 10# light mineral oil; the oiliness agent is pentaerythritol oleate; the extreme pressure anti-wear agent is di-n-butyl phosphite; and the rust inhibitor is dodecenylsuccinic acid.

[0064] The preparation method of the wear-resistant antioxidant of this embodiment comprises the following steps:

[0065] S11, 2g of molybdenum disulfide powder and 100g of N-methylpyrrolidone were added to a reactor, the temperature was raised to 95°C under a nitrogen atmosphere, sheared and stirred at 3000rpm for 30min, ultrasonicated at 50kHz for 2h under a heat preservation state, the supernatant was centrifuged and filtered, vacuum dried, and dialyzed into deionized water to obtain a nanosheet molybdenum disulfide dispersion with a concentration of 5mg / mL;

[0066] S12, dissolving 0.2 g of 2-aminoterephthalic acid in 40 g of N,N'-dimethylformamide, adding 40 mL of a nanosheet molybdenum disulfide dispersion containing 0.2 g of molybdenum disulfide and 0.14 g of nickel nitrate, heating to 80° C. for 10 h, centrifuging and drying under vacuum to obtain a modified metal organic framework;

[0067] S13. Add 0.5 g of the modified metal organic framework to 50 g of xylene, add 0.2 g of carnosic acid, raise the temperature to 130° C. under vacuum conditions, react for 1 h, and remove the xylene by rotary evaporation to obtain a wear-resistant antioxidant.

[0068] A method for preparing a composite lubricant for use in an aluminum rolling process according to this embodiment includes the following steps:

[0069] S1. Filter the base oil and add it to a reactor. Heat it to 60°C. Add an extreme pressure anti-wear agent and a wear-resistant antioxidant. Keep it warm and stir it at 8000 rpm for 1.5 hours. Then add oleic acid diethanolamide, a rust inhibitor and an oiliness agent. Stir it at 1500 rpm for 1.5 hours. Cool and filter it. Fill it into a can to obtain a composite lubricant for aluminum rolling.

[0070] The present embodiment provides an application of a composite lubricating oil for aluminum rolling, which is used for lubricating an aluminum cold rolling mill, and includes the following steps:

[0071] S21. Add the composite lubricating oil used in the aluminum rolling process into an oil tank at a temperature of 60°C, heat and atomize it into 2μm droplets through an oil and gas generator, and then spray it from a nozzle to the contact area between the aluminum plate and the cold rolling mill roller through compressed air at a pressure of 2.5MPa. The roughness of the upper and lower rollers of the cold rolling mill is Ra=1.6μm, and the rolling speed is 500m / min. The oil film thickness is controlled to be 1.2μm.

[0072] Comparative Example 1: The difference between this comparative example and Example 1 is that the wear-resistant antioxidant is replaced by molybdenum disulfide powder.

[0073] Comparative Example 2: This comparative example differs from Example 1 in that the wear-resistant antioxidant is replaced by a modified metal organic framework.

[0074] Comparative Example 3: This comparative example differs from Example 2 in that the wear-resistant antioxidant is replaced by a mixture of molybdenum disulfide powder and carnosic acid in a mass ratio of 3:1.

[0075] Performance Testing

[0076] The flash points of the composite lubricating oils prepared in the Examples and Comparative Examples were measured according to GB / T 267.

[0077] According to GB / T 265-1988 “Determination of kinematic viscosity and calculation of dynamic viscosity of petroleum products”, the kinematic viscosity of the composite lubricating oil prepared in each embodiment and comparative example was measured at 40° C. and 80° C.

[0078] The acid value of the composite lubricating oil prepared in each embodiment and comparative example was measured according to GB / T 264-83.

[0079] The test results are shown in Table 1 below:

[0080] Table 1 Performance test

[0081]

[0082] According to GB / T 3142-2019 "Determination of Load-Carrying Capacity of Lubricants - Four-Ball Method", the surface of the steel ball was completely immersed in the composite lubricating oil prepared in each embodiment and comparative example. The top ball was rotated at 1200 rpm for 1 hour at an oil temperature of 75°C. The maximum no-seizure load, average friction coefficient, and average wear spot diameter of the bottom three balls of each embodiment and comparative example were measured.

[0083] According to GB / T 5096-2017 "Petroleum Products Copper Strip Corrosion Test Method", copper strips were added to the composite lubricating oils prepared in each Example and Comparative Example and immersed at 100°C for 3 hours. The copper strip corrosion level of the composite lubricating oils prepared in each Example and Comparative Example was measured using a copper strip corrosion standard color plate.

[0084] The test results are shown in Table 2:

[0085] Table 2 Friction and corrosion performance test

[0086]

[0087] From the above data, it can be seen that the base oil of Example 1 and Example 3 is PANESTER 0418 synthetic oil, which is polymerized based on poly-α-olefin, has a regular molecular structure, uniform intermolecular forces, and low shear resistance, so the kinematic viscosity is low. The kinematic viscosity of the composite lubricating oil of Example 1 and Example 3 at 40°C is 6.37-6.44 mm 2 / s, kinematic viscosity at 80℃ is 2.62~2.70mm 2 / s; Synthetic oil has almost no light fractions and non-hydrocarbon impurities, is difficult to break to form small molecular volatiles and difficult to oxidize to form organic acids, so the flash point is high and the acid value is low, its flash point is 174-177 ° C, and the acid value is 0.011-0.014 mgKOH / g; The base oil of Example 2 and Example 4 is 10# light mineral oil, which is mainly composed of alkanes, cycloalkanes and aromatic hydrocarbons extracted from natural crude oil, has uneven molecular size, contains branched structure, and has greater shear resistance than synthetic oil. Therefore, the kinematic viscosity of the composite lubricating oil of Example 2 and Example 4 at 40 ° C is 9.83-9.91 mm 2 / s, kinematic viscosity at 80℃ is 4.29~4.37mm 2 / s; a small amount of light fraction and non-hydrocarbon impurities remain in the light mineral oil. The volatilization of the remaining light fraction causes the flash point to be lower than that of the synthetic oil. The non-hydrocarbon impurities will oxidize to form organic acids, resulting in an acid value greater than that of the synthetic oil. Therefore, the flash point is 153-156°C and the acid value is 0.023-0.026 mgKOH / g, indicating that the composite lubricating oil prepared by the present invention can meet the performance requirements in the aluminum rolling process. The maximum no-seizure load of the composite lubricating oils prepared in Examples 1 to 4 is 673-696 N, the average friction coefficient is 0.03, and the average wear spot diameter is 0.59-0.62 mm, indicating that the composite lubricating oil prepared by the present invention has excellent lubrication and wear resistance. The copper sheet corrosion level of the composite lubricating oils prepared in Examples 1 to 4 is all level 1, indicating that the composite lubricating oil prepared by the present invention has excellent corrosion resistance.

[0088] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

[0089] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to specific embodiments. Obviously, many modifications and variations are possible based on the contents of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A composite lubricant for use in an aluminum rolling process, characterized in that: The composition comprises the following components in parts by mass: 94-96 parts of base oil, 0.5-1.5 parts of oiliness agent, 0.5-0.8 parts of extreme pressure anti-wear agent, 0.5-1.5 parts of wear-resistant antioxidant, 0.5-2 parts of oleic acid diethanolamide and 0.5-1 parts of rust inhibitor; The wear-resistant antioxidant is prepared by adding nanosheets of molybdenum disulfide to 2-aminoterephthalic acid and nickel nitrate to react to prepare a modified metal organic framework with molybdenum disulfide intercalation, and then grafting carnosic acid through an amide reaction; The nanosheet molybdenum disulfide is prepared by ultrasonically exfoliating nano-molybdenum disulfide powder. The nanosheet molybdenum disulfide has 1 to 5 layers, a single layer rate of 70 to 80%, and a lateral size of 0.2 to 0.5 μm. The modified metal organic framework is prepared by using 2-aminoterephthalic acid as an organic ligand and nickel nitrate to connect the organic ligand. The molar ratio of molybdenum disulfide to nickel nitrate is (1-2):

1.

2. The composite lubricant for aluminum rolling according to claim 1, characterized in that: The base oil is any one of synthetic oil and light mineral oil; the oiliness agent is any one or more combinations of methyl oleate, pentaerythritol oleate, and trimethylolpropane oleate; the extreme pressure anti-wear agent is any one of zinc dialkyl dithiophosphate and di-n-butyl phosphite; and the rust inhibitor is any one of dodecenylsuccinic acid and barium dinonylnaphthalenesulfonate.

3. The composite lubricant for aluminum rolling according to claim 1, characterized in that: The preparation method of the wear-resistant antioxidant comprises the following steps: S11. Add 1 to 2 parts by mass of molybdenum disulfide powder and 100 to 150 parts of N-methylpyrrolidone to a reaction kettle, heat and shear, stir and disperse under a nitrogen atmosphere, keep warm and perform ultrasonic treatment, centrifuge and filter to obtain the supernatant, vacuum dry, and dialyze in deionized water to obtain a nanosheet molybdenum disulfide dispersion; S12, dissolving 0.1-0.4 parts of 2-aminoterephthalic acid in 30-50 parts of N,N'-dimethylformamide, adding 0.1-0.2 parts of molybdenum disulfide nanosheets and 0.1-0.3 parts of nickel nitrate, heating the mixture for reaction, centrifuging, and vacuum drying to obtain a modified metal organic framework; S13. Add 0.5 to 1 parts of the modified metal organic framework to 50 to 60 parts of xylene by mass, add 0.1 to 0.5 parts of carnosic acid, heat and react under vacuum conditions, remove the xylene by rotary evaporation, and prepare a wear-resistant antioxidant.

4. The composite lubricant for aluminum rolling according to claim 3, characterized in that: The S11 is heated to 90-95° C. under a nitrogen atmosphere, and dispersed by shear stirring at 2000-3000 rpm for 15-30 minutes, and ultrasonicated at an ultrasonic frequency of 30-50 kHz for 0.5-2 hours. The concentration of the molybdenum disulfide dispersion is 1-5 mg / mL.

5. The composite lubricant for aluminum rolling according to claim 3, characterized in that: The molar ratio of 2-aminoterephthalic acid and nickel nitrate in S12 is (1.9-2.5): (1-1.2), and the temperature is raised to 80-90°C for reaction for 10-12 hours; in S13, the temperature is raised to 110-130°C for reaction for 1-2 hours to allow the carboxyl group of carnosic acid to undergo an amide reaction with the amino group of the modified metal organic framework, thereby loading the modified metal organic framework with carnosic acid.

6. The method for preparing a composite lubricant for aluminum rolling according to any one of claims 1 to 5, characterized in that: The steps include: S1. Filter the base oil and add it to a reactor. Heat it to 60-70°C. Add extreme pressure anti-wear agent and wear-resistant antioxidant and stir it at high speed while keeping it warm. Then add oleic acid diethanolamide, rust inhibitor and oiliness agent. Keep it warm and stir it. Cool and filter it. Fill it into a can to prepare a composite lubricant for aluminum rolling.

7. The method for preparing a composite lubricating oil for aluminum rolling according to claim 6, characterized in that: After adding extreme pressure anti-wear agent and wear-resistant antioxidant to S1, high-speed shear stirring is carried out at a speed of 5000-10000 rpm for 1-2 hours. After adding oleic acid diethanolamide, rust inhibitor and oiliness agent, stirring is carried out at a speed of 1000-2000 rpm for 1-2 hours.

8. The use of a composite lubricant in an aluminum rolling process according to any one of claims 1 to 5, characterized in that: For lubrication of aluminum cold rolling mill, including the following steps: S21. Add the composite lubricating oil used in the aluminum rolling process into an oil tank with a temperature of 40-60°C, heat and atomize it into 1-3 μm droplets through an oil and gas generator, and then spray it from a nozzle to the contact area between the aluminum plate and the cold rolling mill roller through compressed air, and control the oil film thickness to 0.5-1.2 μm.

9. The use of a composite lubricant in an aluminum rolling process according to claim 8, characterized in that: The pressure of the compressed air in S21 is 0.5-3 MPa, the roughness of the upper and lower rollers of the cold rolling mill is Ra=1-2 μm, and the rolling speed is 300-500 m / min.

Citation Information

Cited By

  • Mining anchor rod construction technology

    CN121755545A